Design and evaluation of portable emergency ventilator prototype with novel titration methods. (May 2023) - Ding, Bozhi; Xu, Feng; Wang, Jiali; Pan, Chang; Pang, Jiaojiao; Chen, Yuguo; Li, Ke
Highlights: A novel portable emergency ventilator with compact structure and efficient titration were developed in this study. The new ventilator could provide desired tidal volume, ventilation respiratory rate, peak inspiratory pressure, peak inspiratory flow, inspiratory time and expiratory time with satisfactory respiratory waveforms, functioning performance, fast flow supply and accurate parameter control. The new titration method requires less time to complete the titration process and could be used to estimate the lung compliance and airway resistance even at flow mode during the functioning of ventilator. This new ventilator with the new titration approach could play a role in various emergency situations for out-of-hospital, transport or in-hospital first aid. Abstract: Mechanical ventilation is considered to be an effective treatment in cardiopulmonary resuscitation (CPR). Traditional ventilators are not suitable for prompt out-of-hospital first aid treatment due to the limitations of large size and slow titration. This study proposed a novel portable emergency ventilator prototype with compact structure and efficient titration. The prototype was realized by using a centrifugal fan suitable for volume controlled intermittent positive pressure ventilation and pressure controlled intermittent positive pressure ventilation modes. The new titration technique was developed based on the relationships between the PWM and flow. The validity of the new prototype was examined using a test-lung (Michigan A13) in comparison with a commercial ventilator (ResMed Stellar 150) under three simulated lung conditions -- acute respiratory distress syndrome (ARDS), chronic obstructive pulmonary diseases (COPD) and normal lung. Results indicated that the new prototype could provide desired tidal volume, ventilation respiratory rate, peak inspiratory pressure, peak inspiratory flow, inspiratory time and expiratory time with satisfactory respiratory waveforms, functional performance, fast flow supply and accurate parameter control for all three lung conditions. The tidal volume and peak inspiratory flow values were higher than their default values at 500 ml and 33 L, respectively, and the errors were within 10 % of target. The new titration method required only 3 breaths to complete the titration process, which were fewer than the ResMed Stellar 150 that requires at least 5 breaths. The fewer breaths needed for titration may result in shorter response time and could accelerate estimating the lung compliance and airway resistance while running the ventilator. This new prototype with the new titration technique could play a role in various emergency situations for out-of-hospital, transport or in-hospital first aid.